Comparison of conjunctival autograft and amniotic membrane graft in reducing pterygium-induced corneal astigmatism - Rani, Seema; Kour, Manpreet; Rani, Neelam (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Pterygium is a common ocular surface disorder that not only affects cosmesis but also induces corneal astigmatism, leading to visual impairment. This study aimed to compare the effectiveness of CAG and AMG in reducing pterygium-induced corneal astigmatism and to evaluate postoperative complications associated with each technique. Methods: A prospective, comparative study was conducted on 60 patients with primary pterygium at the Upgraded Department of Ophthalmology, GMC, Jammu, from Oct.2016 to April 2017. Patients were randomly assigned to undergo pterygium excision followed by either CAG/AMG. Preoperative and postoperative assessments were conducted at multiple intervals up to six months. Results: Preoperatively, the mean pterygium size was similar in both groups. Postoperatively, corneal astigmatism showed a progressive decline in both groups. By the first postoperative day, astigmatism significantly decreased (p<0.001), with further reductions at one week (p<0.0001). At one month, the conjunctival autograft group demonstrated a slightly greater reduction (0.60±0.61 D) compared to the amniotic membrane group (0.84±0.68 D). By three months, astigmatism remained stable at 0.62±0.62 D and 0.98±0.72 D, respectively. However, the intergroup difference was not statistically significant at any time point (p>0.05), indicating comparable efficacy in postoperative corneal curvature improvement. Postoperative complications were more frequent in the conjunctival autograft group, with significantly higher conjunctival hyperemia (63% vs. 26%, p=0.003), while other complications were comparable between groups. Conclusions: Both conjunctival autograft and amniotic membrane graft effectively reduced corneal astigmatism following pterygium excision.